Is Habituation Measurable in Lumpfish Cyclopterus lumpus When Used as Cleaner Fish in Atlantic Salmon Salmo salar Aquaculture? - Staven, Fredrik R.; Nordeide, Jarle T.; Imsland, Albert K.; Andersen, Per; Iversen, Nina S.; Kristensen, Torstein (Frontiers in Veterinary Science, 2019)
To investigate how lumpfish interact in Atlantic salmon aquaculture, physiological stress responses and changes in behaviour were analysed in experienced and naive lumpfish. Experienced lumpfish (30.2 ± 7.93 g, mean ± SD) coexisted with a commercial scale production unit of Atlantic salmon (1258.5 ± 152.12 g) for 30 to 60 days, while naive lumpfish (38.2 ± 12.37 g) were kept with conspecifics only. Ten trials from each background were tested. For each trial, ten lumpfish were tagged and transferred to a video monitored experimental tank (2 x 2 x 0.7 m). In each trial, swimming behaviour was mapped for all lumpfish every 60 seconds in 20 minutes, ten minutes before and ten minutes after the introduction of four Atlantic salmon. Naive lumpfish expressed significantly increased burst swimming activity and maintained longer interspecific distance to Atlantic salmon in comparison with experienced fish. In addition, mean plasma cortisol levels were significantly elevated in naive fish after exposure to Atlantic salmon. We argue that naive lumpfish expressed innate physiological and behavioural stress responses during first encounter with Atlantic salmon, while reduced responses in experienced individuals indicated habituation. The effect from behavioural and physiological stress in newly deployed naive lumpfish - before and during habituation - should be taken account for when lumpfish are introduced in commercial sea cages to improve welfare for the species. In addition, we suggest that habituation could be applicable during the rearing phase to moderate the transition from a simple tank environment with conspecifics only to interspecies interaction with Atlantic salmon in sea cages.